Authorship, Attribution, and the Changing Ethics of Plagiarism - Bhandari , Nagendra Bahadur (Asian Journal of Population Sciences, 2026)
Plagiarism refers to the practice of using others' ideas and creative works without giving due credit to the original. The advancement in technologies, including artificial intelligence, facilitates the task of extracting and reproducing academic as well as creative content, which in turn problematizes the traditional understanding of originality and authorship. Such practices pose a serious challenge in academia. In such a context, this article draws a brief survey of the historical transformation in the understanding of originality and authorship, examines current practices of plagiarism, and provides some practical strategies and skills for novice researchers and writers to avoid such practices. In doing so, it aims to make young scholars aware of the possible ethical, academic, and legal consequences and uphold academic integrity and ethical practices.